Implement a Real-Time Outdoor Air Pollution Monitoring System Device with Graphical User Interface (GUI) at UTHM Pagoh College - Muhammad Shaqil Norrazman; Rosli, Mohd Arif; Amirul Syafiq Sadun; Wong Kiat Wah (Progress in Engineering Application and Technology, 2025)
Air is a vital element for human survival, but air pollution caused by human activities such as fossil fuel combustion and construction negatively impacts health. At UTHM Pagoh Campus, the absence of a real-time air monitoring system leads to exposure to pollutants without adequate precautions. The objective of this study is to develop a low-cost IoT-based air monitoring system with a graphical user interface (GUI) to record parameters such as Carbon Monoxide (CO), Ozone (O₃), and Nitrogen Dioxide (NO₂) in real time. The study utilizes the ESP32 microcontroller, gas sensors, and the Blynk application to transmit and display data in the cloud. Data was collected near residential colleges over eight hours and one hour to analyze pollution patterns. The findings indicate shows that the average readings of air quality parameters over a 10-minute interval are as follows: Test 1 (NO₂ = 328 µg/m³, O₃ = 161 µg/m³, CO = 27 mg/m³), Test 2 (NO₂ = 318 µg/m³, O₃ = 208 µg/m³, CO = 37 mg/m³), and Test 3 (NO₂ = 111 µg/m³, O₃ = 112 µg/m³, CO = 14 mg/m³). A comparison with New Malaysia Ambient Air Quality Standard (DoE, 2021) guidelines reveals that the readings for NO₂, O₃, and CO in Test 1 and Test 2 exceed the specified limits during conditions of heavy traffic and hot weather. Conversely, the readings in Test 3 comply with the standards during rainy conditions. This project successfully achieved its objectives of developing a monitoring system and identifying air pollution levels. Recommendations include improving monitoring for SO₂ and fine particles such as PM₁₀ and PM₂.₅, which could enhance the system's effectiveness. Therefore, the sensors used such as MQ-131(Ozone), MQ-7(Carbon Monoxide), and MQ-135(Nitrogen dioxide).